Reduced Contrast Sensitivity Function in Central and Peripheral Vision by Disability Glare. (December 2020) - Wu, Di; Liu, Na; Xu, Pengbo; Sun, Kewei; Xiao, Wei; Li, Chenxi
Various glares can decrease visual performance and cause discomfort, thus increasing drivers' risk for traffic accidents in real life. The current study aimed to systematically investigate glare sensitivity in the central and peripheral visual fields by measuring contrast sensitivity function (CSF) under nonglare, steady glare, and transient glare conditions. Nine observers with normal visual acuity in the dominant eye were enrolled. The CSF in central and peripheral vision (the 5° upper left visual field) was measured in a mesopic environment while the stimulus was displayed under three conditions: nonglare, steady glare, and transient glare. An orientation identification task was used to obtain the CSF. After the experiment, the observers were asked to report their level of discomfort in the presence of the glare. The area under the log CSF (AULCSF) and cut-off spatial frequency served as indicators of visual performance. In agreement with previous studies, both steady and transient glare reduced the AULCSF and cut-off frequency. However, the AULCSF and cut-off frequency were reduced more for central vision than for nearly peripheral vision. In addition, the extent of the decreases in the AULCSF and cut-off frequency was greater for steady glare than for transient glare; in contrast, more discomfort was associated with transient glare than steady glare.